Consultation of Bullying Prevention for the Students of Junior High School of Taman Rama Jimbaran - Maria Osmunda Eawea Monny; Evelyn Angelita Pinondang Manurung; Eka Ayu Purnama Lestari (Community Service Journal of Law, 2022)
This social engagement is done in order to give information to the students of Taman Rama Jimbaran Junior High School (TRJ-JHS) about how to prevent bullying action. This socialization is important to be implemeted considering that in this school in this school there are variety of students’ backgrounds like nations, ethnics, cultures, religions and others. The solution to solve this fact is by giving the students information about kinds and impacts of bullying for the victims and perpetractors. This is important because sometimes students considering that their actions are just something ordinary for example Iike a joke among them but to some extend it can be forms of bullying that can give negative impact to other students or person. Method in this social engagement is used was online conference through Zoom. Main findings of this social engagement are: the eagerness of the students to know the information about bullying and the enthusiasm of Principle and teachers as a form of their attention for bullying and how to prevent it. The students were able to grasp the information by asking questions needed. There were 52 participants in this activity, those were Principle, teachers and students. Finally, the information about bullying prevention is expected to be applied properly and appropriately by students and all parties involved in it.